Indonesia Negara Hukum dan Politik Yang Berbasis Demokrasi - Ama, Jefrianus Tamo; Kadir, Syukron Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Indonesia is a legal state with a country that adheres to the continental European legal system. Where this is all sources of law based on the 1945 Constitution as the highest law of the Indonesian nation. The concept of the Indonesian rule of law is intended to form an Indonesian state government that protects the entire Indonesian nation and all of Indonesia's blood. This means that the concept of a rule of law is contained in the preamble to the 1945 Constitution. Law and politics are two different forms, but have a close relationship. Because law originates from the results of political power. and politics itself is an institution of authorized politicians who produce regulations. Law and politics have a very close relationship. The formation of a legal regulation of a political force. The relationship between law and politics cannot be separated from the conditions of society in a country, so this is like a chain that is always connected, even like a symbiotic mutualism, namely mutual dependence, that is, law will depend on political conditions, and politics depends on conditions. society. In a democratic country, political power is the state's ability to make other parties act in accordance with state decisions, and the ability of other parties to influence the process of making and implementing state decisions, including the ability to oppose the state.